Potensi Daerah Purwokerto (Analisis Kesiapan Menjadi Kota Purwokerto) - Sri Nugroho; Suprapto Suprapto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
This article was related to the effort of Banyumas Regency be autonomous two separate region; Banyumas Regency and Purwokerto Town. The isues to make Purwokerto Town be autonomous region needed a sufficient kind analyses. It is about what 4 districs in Purwokerto region is suitable be autonomous area. Otherwise, the analyses should include what the rest of districs in Banyumas is keep stand away to be outonopmus regency. Central java at south zone need economics growth centrals. Now, economic growth in Central Java is concentrated at north area. The aglomeration, at least in one local otonomous, is desired growing up the acceleration of economics growth arround the area. Formally, the measurement of local potency should be use the current act, Peraturan Pemerintah No 129/2000 about Persyaratan Pembentukan dan Kriteria Pemekaran, Penghapusan, dan Penggabungan Daerah. Application the rule to measure Banyumas potency, it is finally gained that 4 districs in Purwokerto town is eligible to be autonomous area, but not for the rest districts in Banyumas. Keywords: autonomous area, economic growth, acceleration, Banyumas potency